Animal breeding and genetics online course - CGIAR Research Program on Livestock (2017)
Seven week course developed with Wageningen University and Research for students to understand the genetic and statistical principles that enable responsible animal breeding. The course was developed with financial support and input from the Koepon Foundation (http://www.koeponstichting.nl/) and the ILRI managed African Chicken Genetic Gains project (https://africacgg.net/.) Website: https://www.edx.org/course/animal-breeding-and-genetics